VD_FINDINFO Pron / 2014 / 23 vom 19. Februar 2014 - VD Tribunal cantonal (2014)
PROTECTION DE L'UNION CONJUGALE, CONJOINT, OBLIGATION D'ENTRETIEN, TRANSACTION JUDICIAIRE | 105 al. 1 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 4 TFJC (2010), 67 al. 2 TFJC (2010)